Existence and Multiplicity of Solutions for Semipositone Problems Involving p-Laplacian - Guowei Dai; Chunfeng Yang (International Journal of Mathematics and Mathematical Sciences)
We prove existence and multiplicity of positive solutions for semipositone problems involving p-Laplacian in a bounded smooth domain of ℝN under the cases of sublinear and superlinear nonlinearities term.